Effects of Discontinuation of Drugs Used for Augmentation Therapy on Treatment Outcomes in Depression: A Systematic Review and Meta-analysis - Kato, Hideo; Koizumi, Teruki; Takeuchi, Hiroyoshi; Tani, Hideaki; Mimura, Masaru; Uchida, Hiroyuki (Pharmacopsychiatry, 2020)
Introduction There has been no consensus on whether and how long add-on drugs for augmentation therapy should be continued in the treatment of depression.Methods Double-blind randomized controlled trials that examined the effects of discontinuation of drugs used for augmentation on treatment outcomes in patients with depression were identified. Meta-analyses were performed to compare rates of study withdrawal due to any reason, study-defined relapse, and adverse events between patients who continued augmentation therapy and those who discontinued it.Results Seven studies were included (n=841 for continuing augmentation therapy; n=831 for discontinuing augmentation therapy). The rate of study withdrawal due to any reason was not significantly different between the 2 groups (risk ratio [RR]=0.86, 95% confidence interval [CI]=0.69–1.08, p=0.20). Study withdrawal due to relapse was less frequent in the continuation group than in the discontinuation group (RR=0.61, 95% CI=0.40–0.92, p=0.02); however, this statistical significance disappeared when one study using esketamine as augmentation was excluded. Analysis of the data from 5 studies that included a stabilization period before randomization found less frequent relapse in the continuation group than in the discontinuation group (RR=0.47, 95% CI=0.36–0.60, p<0.01). This finding was repeated when the esketamine study was excluded.Discussion No firm conclusions could be drawn in light of the small number of studies included. Currently available evidence suggests that add-on drugs, other than esketamine, used for augmentation therapy for depression may be discontinued. This may not be the case for patients who are maintained with augmentation therapy after remission.
Keywords: antidepressant; augmentation; depression; ketamine; relapse